Development of a software application for the execution of the quantitative association rules mining algorithm (QUARG) - Cubillo-Rojas, Adalberto (2012)
Proyecto de graduación (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2012